Clinical-radiological comparative evaluation of the BISAP and Computed tomography severity index scores as predictors of severity in acute pancreatitis - Nasreen Aman; Nosheen Noor; Muhammad Hamza; Hamna Khalid (Pakistan Journal of Medical Sciences, 2026)
Objectives: To compare the clinical and radiological performance of the Bedside Index for Severity in Acute Pancreatitis (BISAP) and the Computed Tomography Severity Index (CTSI) in predicting disease severity and mortality in patients with acute pancreatitis, providing locally relevant evidence from a tertiary care setting in Pakistan. Methodology: This retrospective cross-sectional study was conducted at the Department of Radiology, Lady Reading Hospital–MTI, Peshawar, from January to December 2024. Data from 99 adult patients diagnosed with acute pancreatitis according to the Revised Atlanta Criteria (2012) were analyzed. BISAP scores were calculated using clinical and laboratory parameters recorded within 24 hours of admission, while CTSI was derived from contrast-enhanced CT findings. Disease severity was dichotomized into severe and non-severe categories for receiver operating characteristic (ROC) curve analysis. Diagnostic accuracy, optimal cut-off values, and predictive performance of BISAP and CTSI for severity and in-hospital mortality were assessed. Results: Out of 99 patients, severe acute pancreatitis was identified in 35.4% by CTSI and 20.2% by BISAP scores. ROC analysis demonstrated superior predictive performance of BISAP scores for severe acute pancreatitis with an area under the curve (AUC) of 0.667 (95% CI: 0.559–0.775; p = 0.006), compared to CTSI scores with an AUC of 0.571 (95% CI: 0.456–0.686; p = 0.239). For mortality prediction, BISAP scores showed better discrimination (AUC 0.846; 95% CI: 0.677–1.000; p = 0.021) with 100% sensitivity at the optimal cut-off, whereas CTSI scores demonstrated poor predictive ability (AUC 0.528; p = 0.852). Conclusion: BISAP demonstrated better predictive performance than CTSI in this cohort and may be a useful bedside tool for early risk stratification. CTSI remains valuable for assessing local pancreatic complications but has limited prognostic utility when used alone.